Belonging in translation : solidarity and migrant activism in Japan - Shindo, Reiko (Global migration and social change., 2019)
This is the first book to investigate how migrants and migrant rights activists work together to generate new forms of citizenship identities in a multilingual setting. Based on robust theoretical engagement and detailed empirical analysis, Shindo's book makes a compelling case for rethinking citizenship and community from the angle of language.